Kemampuan Menulis Nama-Nama Hewan Dalam Tulisan Arab Melayu Mahasiswa Program Studi Pendidikan Bahasa Dan Sastra Indonesia - Hasnah Faizah; Novi Damaiyanti; Nadia Armanda (BADAN PENERBIT STIEPARI PRESS, 2024)
The development of the times means that the Riau Malay people no longer use Malay Arabic in their daily lives, so it is necessary to preserve the cultural heritage of the Riau Malay people. The aim of this research is to determine the average category of ability to write animal names in Malay Arabic writing for students of the Indonesian language and literature education study program. The type of research used is quantitative research using quantitative descriptive methods. The data collection technique was carried out using a written test technique. The data analysis technique in this research is quantitative descriptive data analysis technique. Based on the research results, of the 25 samples there were 3 students who got the very good category with a percentage of 12%, 10 students who got the good category with a percentage of 40%, 11 students who got the fair category with a percentage of 44%, 1 student who got the poor category with a percentage 4%, and no students received the need for guidance category. The conclusion is that the average student ability in writing Malay Arabic is 67.6 in the good category.